Orthostatic Hypotension Management in Patients with Traumatic Cervical Myelopathy - Fedor A. Bushkov; Alexander N. Razumov; Nino V. Sichinava (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
Aim. To study the incidence and severity of orthostatic hypotension and develop a method for its correction in patients after spinal cord injury (SCI) at the cervical level. Material and мethods. The study included 120 patients after spinal cord injury at cervical level with tetraplegia C5-C8 motor levels since injury more than 1 year divided into 3 groups comparable in terms of demographic, neurological and functional parameters. The group 1 (control) received standard therapy (exercise therapy, modalities, ergotherapy, massage), the group 2 received standard therapy and permanent wearing of an abdominal bandage during the day, the group 3 received rehabilitation identical to the group 2 in conjunction with low-intensity laser therapy (reflex-segmental technique). Evaluation of the results was carried out at the beginning (T1), at the end (T2) after a 30-day rehabilitation course; in assessing the state of the ANS used heart rate variability, ABPM, tilt test, deep breathing test; the motor system was assessed using the international neurological assessment standard - ASIA Impairment Scale, the FIM motor subscale (FIMm). Results and discussion. The quantity of 35% of patients have orthostatic hypotension while subjective manifestations during the tilt test was seen only in 22% of patients. At the initial examination, there were no differences between the groups in terms of vegetative and functional status. There were no changes in neurological status in all groups, functional activity increased by 6 ± 5.4 points in the control group (FIMm), and 6 ± 4.6 and 7 ± 4.5 points in 2 and 3 groups, respectively without any the statistical differences between the groups (F = 0.51; p = 0.42) at the end of rehabilitation. There were positive changes in vegetative parameters in all groups, with the exception of the mean night systolic blood pressure (SBP) between the 1 and 2 groups. Intergroup comparison have shown positive changes in all vegetative parameters that was higher in the 2 and 3 groups: decreasing drop of SBP during tilt test was 4 ± 2.8. and 5 ± 3.2 mm Hg, increase in inspiratory- expiratory index (RRmax / RRmin) 0.5 ± 0.08 and 0.7 ± 0.10 units, increase in daytime mean SBP (ABPM) 5 ± 1.1 and 8 ± 1.4 mm Hg respectively in groups 2 and 3, against 2 ± 1.9 mm Hg. and 0.2 ± 0.05 units, 3 ± 0.9 mm Hg in the group 1. In group 3, the value and increase in RRmax / RRmin (1.21 ± 0.11; 1.23 ± 0.13; 1.27 ± 0.15, respectively, in 1, 2 and 3 groups), mean daytime SBP (105 ± 3; 108 ± 3; 110 ± 4 mm Hg, respectively in 1, 2, and 3 groups) was higher in the group 3. Conclusion. Orthostatic Hypotension (OH) occured in one third of patients in the late period after SCI at the cervical level, the method of OH management that included daytime abdominal bandage wearing and using low-intensity laser radiation (905 nm, 50 Hz) on the cardioreflex zones has shown its preliminary effectiveness.